Pengaruh Penyuluhan Kesehatan Perilaku Hidup Bersih dan Sehat Terhadap Tingkat Pengetahuan Ibu Yang Memiliki Balita Diare - Hana Nurhanifah Budiadi; Niknik Nursifa; Rudi Karmi (Politeknik Baubau, 2025)
The Indonesian Health Profile report on the prevalence of diarrhea among children under five in West Java in 2018 was 46.35% and increased in 2019 to 47.6%. Based on this data, the prevalence of diarrhea in West Java is included in the top 10 provinces with the highest diarrhea cases in Indonesia. Research suggests that the incidence of diarrhea in toddlers in general is the habit of mothers who do not apply PHBS while caring for their babies which results in babies tending to experience diarrhea. The purpose of this study was to determine the effect of health counseling on Clean and Healthy Living Behavior (PHBS) on the level of knowledge of mothers who have diarrhea toddlers. This study used a quasi-experimental research design, namely a study by conducting activities to determine the effect of PHBS health counseling on the level of knowledge of mothers who have diarrhea toddlers with a one group pre-test post-test design which is an experimental research design without a comparison group. The population was 20 respondents and total sampling was taken. The results of the analysis obtained using the Marginal Homogeneity test obtained a p value = 0.000, p value = 0.000 < α (0.05), then Ho is rejected and Ha is accepted, meaning that there is an influence of health counseling on clean and healthy living behavior (PHBS) on the level of knowledge of mothers who have toddlers. There is an effect of PHBS health counseling on the level of knowledge of mothers who have diarrhea toddlers with a value of 0.000.